Konsep Pendidik Dalam Perspektif Pendidikan Islam - Karnada Nasution; Zubaidah Pulungan (GHIROH, 2023)
Educators play an important role in achieving the success of the educational process. Educators are required to always maximize their role in carrying out their duties as mentors, directors, and facilitators of educational success, especially the success of students both in cognitive and psychomotor attitudes. Today, we see and find many cases of educators who have lost their way and run away from their essence as educators who should educate wholeheartedly and show exemplary but contrary to their real functions and roles. The method used in this research is qualitative research method with a type of library research that is collecting sources of journal books and theses are used as references in this research.